(x-5)2-9=0

Add 9 to both sides of the equation.

(x-5)2=9

Take the square root of each side of the equation to set up the solution for x

(x-5)2⋅12=±9

Remove the perfect root factor x-5 under the radical to solve for x.

x-5=±9

Rewrite 9 as 32.

x-5=±32

Pull terms out from under the radical, assuming positive real numbers.

x-5=±3

x-5=±3

First, use the positive value of the ± to find the first solution.

x-5=3

Move all terms not containing x to the right side of the equation.

Add 5 to both sides of the equation.

x=3+5

Add 3 and 5.

x=8

x=8

Next, use the negative value of the ± to find the second solution.

x-5=-3

Move all terms not containing x to the right side of the equation.

Add 5 to both sides of the equation.

x=-3+5

Add -3 and 5.

x=2

x=2

The complete solution is the result of both the positive and negative portions of the solution.

x=8,2

x=8,2

Solve Using the Square Root Property (x-5)^2-9=0